Lymph Node Metastases in Papillary and Medullary Thyroid Carcinoma Are Independent of Intratumoral Lymphatic Vessel Density. Issue 2 (17th April 2017) - Pereira, Filipe; Pereira, Sofia S.; Mesquita, Marta; Morais, Tiago; Costa, Madalena M.; Quelhas, Pedro; Lopes, Carlos; Monteiro, Mariana P.; Leite, Valeriano
Abstract : Background: Blood and lymph vessel invasion are well-recognized markers of tumor aggressiveness, as these are the routes that lead to metastases. Thyroid tumors, depending on the histological variant, tend to have distinctive biological behaviors and use different vascular routes to metastasize, yet the mechanisms underlying the metastatic process are still poorly understood. Objectives: The aim of this study was to assess how the lymph vessel density (LVD) in different histological types of thyroid tumors, and in their surrounding tissue, correlate with the presence of lymph node metastases (LNM) and tumor pathological features. Methods: Lymph vessels of papillary thyroid carcinomas (PTC), of the classical (CVPTC, n = 50) and follicular variants (FVPTC, n = 18), and medullary thyroid carcinomas (MTC, n = 34) were immunohistochemically stained against antigen D2-40. The stained area was quantified using a computerized morphometric analysis tool and correlated with the tumor pathological characteristics. Results: LVD within all analyzed thyroid tumor subtypes was significantly lower than in the surrounding thyroid tissues ( p < 0.001). Despite intratumoral LVD being significantly higher in CVPTC than in FVPTC, and peritumoral LVD being significantly higher in MTC than in PTC ( p < 0.05), no correlations were found between LVD (either intratumoral or peritumoral) and the presence of lymph node metastasis. Conclusions: As no LVD differences were found amongst thyroid tumors with or without LNM, dissemination is more likely to depend on the tumor ability to invade the abundant lymph vessel network of the surrounding thyroid tissue than on the ability of the tumor to promote de novo lymphangiogenesis.